Patriots, royalists, and terrorists in the West Indies : the French Revolution in Martinique and Guadeloupe, 1789-1802 - Cormack, William S. (University of Toronto Press, 2019)
This book provides a history of the French Revolution in Martinique and Guadeloupe from 1789 to 1802. Examining political conflict between white factions, as well as economic, social, and racial tensions, it argues that metropolitan news, ideas, language, and political culture played a key role in shaping the colonial revolution.